What has not yet been said about Prussian proper names in Polish lands - Blažienė, Grasilda (Vilnius University Open Series, 2022)
The research of historical proper names reveals the necessity to emphasize and link the cultural, social and political aspects that play a role in the development of onyms. It should be noted that the language and the names of inhabited settlements reflecting it developed within a certain single system of life, which can be divided only hypothetically. The oikonymy of the extinct language, when viewed as the development of linguistic phenomena, should be addressed from a systematic perspective. It is impossible to draw the line that would divide the starting point and the end point of the development of historical proper names. The rich empirical data, mostly coming from historical manuscript sources, show an ongoing process. We cannot tell the exact date when the Old Prussian language became extinct. However, it is clear that the Old Prussian names of inhabited settlements outlived the language and were more resistant to the processes of Germanization and Polonization than it has been thought to this day. Linguistic, social and cultural phenomena occur in the same domain and are mutually dependent. Politics has the power to change the name. The replacement of some of East Prussia’s native toponyms with Russian ones is a sad proof of that power put into practice. Nevertheless, some indigenous toponyms had enough strength to survive. The dimension of historical time has been introduced to the research and the significance of change for the survival of Old Prussian proper names in the processes of Germanization and Polonization has been highlighted. Polish onomasticians also study the extralinguistic meaning of onyms through the heritage of the Teutonic Order, as onyms are the witnesses of history in the environment of language contacts. The monumental work of Polish researchers Nazwy miejscowe Polski (Eng. Polish Place Names) is also noteworthy, however, the material that is included or excluded occasionally poses quite a few questions for the researchers of Old Prussian proper names. The article discusses more interesting cases of Old Prussian oikonymy on the territory of present-day Poland.
Keywords: Old Prussian proper names; historical sources; Old Prussian oikonyms; change; fixation; Polonization